2015
DOI: 10.1016/j.jpeds.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Advancing Gestation and Non-Caucasian Race on Ductus Arteriosus Gene Expression

Abstract: Objective To identify genes affected by advancing gestation and racial/ethnic origin in human ductus arteriosus (DA). Study design We collected three sets of DA tissue (n=93, n=89, n=91; total = 273 fetuses) from second trimester pregnancies. We examined four genes, with DNA polymorphisms that distribute along racial lines, to identify "Caucasian" and "Non-Caucasian" DA. We used RT-PCR to measure RNA expression of 48 candidate genes involved in functional closure of the DA, and used multivariable regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…18 One striking finding is the different ethnic response to cyclooxygenase inhibitor treatment. 19 Our study has only been conducted in a single centre and is therefore unable to examine those relationships. Furthermore, only one polymorphism has been examined and it cannot be excluded that other vascular endothelial growth factor polymorphisms modify ductal closure or pharmacological treatment response.…”
Section: Discussionmentioning
confidence: 98%
“…18 One striking finding is the different ethnic response to cyclooxygenase inhibitor treatment. 19 Our study has only been conducted in a single centre and is therefore unable to examine those relationships. Furthermore, only one polymorphism has been examined and it cannot be excluded that other vascular endothelial growth factor polymorphisms modify ductal closure or pharmacological treatment response.…”
Section: Discussionmentioning
confidence: 98%
“…(24) Waleh et al showed that the expression of SLCO2A1 and NOS3 decreased the success of indomethacin and ibuprofen in ductus closure by increasing the prostaglandin synthesis in the Caucasian race. (25) Waleh et al demonstrated that three calcium and potassium-channel genes (CACNA1G/ alpha1G, CACNB2/CaL-beta2, and KCNA2/Kv1.2), were associated with prostaglandin inhibition and emphasized the consideration of these genes in the development of future medical treatment strategies for PDA closure. (26) In another study, Mangones et al investigated the prevalence of congenital heart diseases (CHD) and showed that PDA was most commonly seen in non-hispanic whites.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 This is consistent with a number of other studies implying that it may play an important role in ductal transition. [21][22][23][24] In addition, in several human gene polymorphism studies, specific TFAP2B and PTGER4 SNPs were associated with PDA in term and preterm infants, 5,25,26 although another study detected no such association of TFAP2B or AGTR1 SNPs with PDA. 27 Another gene, DLX1, a transcription factor expressed in the embryonic caudal pharyngeal arch complex, where the ductus develops, has been hypothesized to direct BMP4 expression to cause vascular remodeling in DA during late gestation.…”
Section: Discussionmentioning
confidence: 99%